β-Ginkgotides: Hyperdisulfide-constrained peptides from Ginkgo biloba - Wong, Ka Ho (2017)
Hyperdisulfide-constrained peptides are distinguished by their high stability and diverse functions. Thus far, these peptides have been reported from animals only but their occurrence in plants are rare. Here, we report the discovery, synthesis and characterization of a hyperdisulfide-constrained peptides family of approximately 2 kDa, β-ginkgotides (β-gB1 and β-gB2) from Ginkgo biloba. Proteomic analysis showed β-ginkgotides contain 18‒20 amino acids, of which 16 residues form a conserved six-cysteine core with a highly clustered cysteine spacing of C‒CC‒C‒CC, an arrangement that has not been reported in cysteine-rich peptides. Disulfide mapping revealed a novel disulfide connectivity of CysI‒IV, CysII‒VI and CysIII‒V. Oxidative folding of synthetic β-gB1 to the native form was obtained in 70% yield. The synthetic β-gB1 displays a compact structure with no regular secondary structural elements, as determined by NMR spectroscopy. Transcriptomic analysis showed precursor βgb1 has a four-domain architecture and revealed an additional 76 β-ginkgotide-like peptides in 59 different gymnosperms, but none in angiosperms. Phylogenetic clustering analysis demonstrated β-ginkgotides belong to a new cysteine-rich peptide family. β-Ginkgotide is resistant to thermal, chemical and proteolytic degradation. Together, β-ginkgotides represent the first-in-class hyperdisulfide-constrained peptide family from plants with a novel scaffold that could be useful for engineering metabolically stable peptidyl therapeutics.